2023
DOI: 10.1080/14756366.2022.2155639
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in chemistry and bioactivity of monoterpenoid indole alkaloids from the genus gelsemium : a comprehensive review

Abstract: Monoterpenoid indole alkaloids (MIAs) represent a major class of active ingredients from the plants of the genus Gelsemium . Gelsemium MIAs with diverse chemical structures can be divided into six categories: gelsedine-, gelsemine-, humantenine-, koumine-, sarpagine- and yohimbane-type. Additionally, gelsemium MIAs exert a wide range of bioactivities, including anti-tumour, immunosuppression, anti-anxiety, analgesia, and so on. Owing to their fascinating structures and potent pharmaceuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 92 publications
1
10
0
Order By: Relevance
“…3000 members) with diverse biological activities and intricate skeletal diversity. 1–7 They continue to influence the research fields of natural products, drug discovery, biochemistry, and especially organic chemistry (total synthesis and methodology development). 8,9 Structurally, the direct covalent C3–C2′ linkage of indole (in blue) with piperidine (in red) characterizes this subclass of alkaloids and thus has sparked great interest from generations of organic chemists in developing novel and efficient synthetic strategies 10–40 (Scheme 1c).…”
Section: Introductionmentioning
confidence: 99%
“…3000 members) with diverse biological activities and intricate skeletal diversity. 1–7 They continue to influence the research fields of natural products, drug discovery, biochemistry, and especially organic chemistry (total synthesis and methodology development). 8,9 Structurally, the direct covalent C3–C2′ linkage of indole (in blue) with piperidine (in red) characterizes this subclass of alkaloids and thus has sparked great interest from generations of organic chemists in developing novel and efficient synthetic strategies 10–40 (Scheme 1c).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have characterized the phytochemical profile of Gelsemium plants [ 2 , 3 , 4 ]. These reports describe the species as a rich source of natural compounds, including iridoids, coumarins, steroids, and alkaloids.…”
Section: Introductionmentioning
confidence: 99%
“…Studies using purified indole alkaloids have shown many biological effects in both in vitro and in vivo assays [ 2 , 3 , 4 ]. These actions range from antitumor activity to antioxidant and anti-inflammatory effects [ 2 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…More than 120 alkaloid compounds have been successfully obtained and determined from the stems, leaves, and roots of plants in the genus Gelsemium , of which more than 80 are indole and hydroxyindole alkaloids [14‐17] . Gelsemium monoterpenoid indole alkaloids are classified into six classes based on their chemical structures: gelsedine, gelsemine, humantenine, koumine, sarpagine, and yohimbane [18] . Among them, koumine is a monoterpene indole alkaloid with the highest content among Gelsemium alkaloid monomers, followed by gelsemine [19] .…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] Gelsemium monoterpenoid indole alkaloids are classified into six classes based on their chemical structures: gelsedine, gelsemine, humantenine, koumine, sarpagine, and yohimbane. [18] Among them, koumine is a monoterpene indole alkaloid with the highest content among Gelsemium alkaloid monomers, followed by gelsemine. [19] These two alkaloids are rapidly absorbed and eliminated, can penetrate the blood-brain barrier, and are widely distributed in all tissues, including the brain.…”
mentioning
confidence: 99%